The diagnostic yield of ultrasound of the head in healthy infants presenting with the clinical diagnosis of benign macrocrania. Issue 1 (January 2017) - Naffaa, L.; Rubin, M.; Stamler, A.C.; Haddad, M.; Saade, C.
Abstract : Aim: To investigate the frequency of sonographic findings that required neurosurgical consultation for all referred outpatients suspected to have benign macrocrania (BMC). Materials and methods: A retrospective review was performed from September 2011 until June 2015 for all outpatients referred to the ultrasound (US) department for BMC. Electronic medical records, US images, and reports were reviewed in conjunction with follow-up imaging. Each review consisted of gender, specialty of referring physician, first head circumference, head circumference at or closest to the time of the head US, the last head circumference, and any neurological issue prior to the US, at the time of US, or following the US, and clinical outcomes. Statistical analysis employed the Kruskal–Wallis rank sum test and Fischer's exact test (chi square test of independence) that compared normal/BMC patients from the patients requiring a neurosurgical consultation. Results: One hundred and thirty (40.9%) had a normal head US, 181 patients (56.9%) had sonographic findings of BMC, and seven (2.2%) patients had an abnormal head US that required a neurosurgical consultation. Of the 181 patients with BMC, 23 underwent follow-up imaging with 22 patients having unchanged BMC or a normal head US and one patient developing mild ventriculomegaly that was stable on follow-up imaging. Three of the seven patients (1%) aged 1.8, 2.3, and 13.1 months with abnormal head US requiring neurosurgical consultation, had mild ventriculomegaly that was stable on follow-up imaging. Four of the seven patients (1.2%) that required neurosurgical consultation needed a neurosurgical procedure. Between the two US subgroups (normal and BMC), no statistical significance was noted regarding age of patient at US, head circumference at clinical and radiological presentation ( p >0.05) except for the first head circumference clinically documented which demonstrated statistical significance ( p <0.03). Conclusion: Short interval surveillance including head circumference and assessment for the development of bulging anterior fontanelle and neurological abnormalities may be more cost effective than US in the initial evaluation of patients clinically suspected to have BMC. Highlights: Benign macrocrania is one of the most common cause of pediatric consultation and neurosonography which helps confirming the diagnosis. Short interval surveillance with head circumference and for development of neurological abnormalities may be more cost effective than US in initial evaluation of patients clinically suspected to have benign macrocrania.